Neurovascular adaptations modulating cognition, mood, and stress responses - Campbell, Matthew (My University, 2023)
The neurovascular unit (NVU) is a dynamic center for substance exchange between the blood and the brain, making it an essential gatekeeper for central nervous system (CNS) homeostasis. Recent evidence supports a role for the NVU in modulating brain function and cognition. In addition, alterations in NVU processes are observed in response to stress, although the mechanisms via which they can affect mood and cognitive functions remain elusive. Here, we summarize recent studies of neurovascular regulation of emotional processes and cognitive function, including under stressful conditions. We also highlight relevant RNA-sequencing (RNA-seq) databases aiming to profile the NVU along with innovative tools to study and manipulate NVU function that can be exploited in the context of cognition and stress research throughout development, aging, or brain disorders.
PUBLISHED
cited By 7